Power and upgrading in global value chains: A case study of a Sri Lankan apparel manufacturer - Gunaratne, D.C.; Balagae, A. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This paper provide a contextualised explanation for power, upgrading practices and upgrading in apparel global value chains (GVCs). It raises questions of how the bargaining power of lead buyers shapes the upgrading of developing country suppliers and how these suppliers manage buyers’ bargaining power using upgrading practices. It deploys insights from the Global Value Chain and Relational Economic Geography literature. A qualitative case study was employed, based on a Sri Lankan apparel manufacturer. Findings suggest the importance of buyers’ bargaining power to shape the suppliers’ upgrading, and the importance of upgrading practices—trust and credibility, diversification and strategic intent—and upgrading to manage buyers’ bargaining power. The paper (re)conceptualises upgrading as an outcome of buyers’ bargaining power and upgrading practices and suggests an approach—for developing country suppliers—to manage buyers’ power through upgrading practices.
Keywords: Power, upgrading, upgrading practices, apparel Global Value Chains, Sri Lanka